Theology and Social Empowerment of Marginal Subcultures: A Study on Pondok Tasawuf Underground Jakarta - Hasby, Muhammad Subky; Arifin, Syamsul; Kholish, Moh. Anas; Suroiyah, Evi Nurus (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study examines the theological principles underlying the social empowerment efforts implemented for the punk community at Pondok Tasawuf Underground Jakarta, focusing on articulating theological values in the context of empowerment and their implementation in daily life. Employing a qualitative phenomenological approach, several data in this study were collected through in-depth interviews with the founder and members of the punk community, participatory observation, and document analysis. The findings reveal that the theological principles underlying empowerment at Pondok Tasawuf Underground are rooted in holistic hijrah, encompassing both spiritual and social transformation. The